2016
DOI: 10.1016/j.ygyno.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the FAM19A4 / mir124-2 DNA methylation test for both lavage- and brush-based self-samples to detect cervical (pre)cancer in HPV-positive women

Abstract: ObjectivesDNA methylation analysis of cancer-related genes is a promising tool for HPV-positive women to identify those with cervical (pre)cancer (CIN3+) in need of treatment. However, clinical performance of methylation markers can be influenced by the sample type utilized. We describe a multiplex quantitative methylation-specific PCR that targets FAM19A4 and mir124-2 loci, to detect CIN3+ using both HPV-positive lavage- and brush self-samples.MethodsWe determined methylation thresholds for clinical classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 52 publications
(85 reference statements)
4
99
0
1
Order By: Relevance
“…Cervical cancer development after a persistent infection with high‐risk HPV is driven by additional host cell changes such as altered DNA methylation 12, 17, 20, 21. In earlier work, we have shown that methylation assays targeting FAM19A4 and/or mir124‐2 genes have competitive performance against other triage options 22, 23, 24, 25, 26. In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24.…”
Section: Introductionmentioning
confidence: 97%
“…Cervical cancer development after a persistent infection with high‐risk HPV is driven by additional host cell changes such as altered DNA methylation 12, 17, 20, 21. In earlier work, we have shown that methylation assays targeting FAM19A4 and/or mir124‐2 genes have competitive performance against other triage options 22, 23, 24, 25, 26. In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24.…”
Section: Introductionmentioning
confidence: 97%
“…The performance of HPV16/18 genotyping has been evaluated on both lavage-and brush-based selfsamples of hrHPV-positive non-attendees, revealing an accuracy which appears to be comparable to cervical scrapes (≥CIN3 sensitivity 65.4-69.4%, specificity 65.0-70.9%, PPV 25.0-48.5%, NPV 85.4-92.4% [80,81]). It is obvious thatregardless of sample type -HPV16/18 genotyping does not suffice as a direct stand-alone triage strategy for hrHPV-positive women, but the combination of HPV16/18 genotyping with other tests has been frequently suggested.…”
Section: Molecular Triage Strategiesmentioning
confidence: 99%
“…Therefore, host cell DNA methylation analysis might be of value as a marker for the detection of cervical (pre)cancer among hrHPV-positive women [32,92]. A variety of methylation markers has been studied in clinical cohorts of hrHPVpositive women [51,80,81,96,97,99,[102][103][104][105][106]. In general, these studies were cross-sectional or had a short-term follow-up and the majority of studies were performed in nonscreening cohorts.…”
Section: 22mentioning
confidence: 99%
See 2 more Smart Citations